2009
DOI: 10.1073/pnas.0907844106
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome evidence reveals successful Late Paleolithic settlement on the Tibetan Plateau

Abstract: Due to its numerous environmental extremes, the Tibetan Plateau-the world's highest plateau-is one of the most challenging areas of modern human settlement. Archaeological evidence dates the earliest settlement on the plateau to the Late Paleolithic, while previous genetic studies have traced the colonization event(s) to no earlier than the Neolithic. To explore whether the genetic continuity on the plateau has an exclusively Neolithic time depth, we studied mitochondrial DNA (mtDNA) genome variation within 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
176
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(193 citation statements)
references
References 34 publications
14
176
0
3
Order By: Relevance
“…43 The ages of the lineages G2a2 (further defined by mutation 16193 and named G2a2 tentatively) and M9a1a2a (characterized by mutations 16145, 16316 and a back mutation at site 16362, and designated as M9a1a2a) (Table 4) were estimated by using the r statistic 44,45 with the suggested calibration rates. 44,46 RESULTS AND DISCUSSION On the basis of the combined information from control-region and partial coding-region segments, the majority (96.34%; 237/246) of the Nepalese mtDNAs could unambiguously be allocated into the defined haplogroups of East Eurasian (36.59%; 90/246), 1,[20][21][22][23][24][25] Table S1, Supplementary Material online), 5 and this pattern remains almost stable for both the East Eurasian (45.11%; 189/419) and South Asian (47.49%; 199/419) components after taking into account the recently reported Nepalese mtDNA data. 5 As for the 21 samples with ambiguously phylogenetic status, completely sequencing their mtDNA genomes revealed that virtually all of these samples in fact belong to the already defined haplogroups, such as M3, M5, M18, M30, M35, M43, D4, R8 and M60.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…43 The ages of the lineages G2a2 (further defined by mutation 16193 and named G2a2 tentatively) and M9a1a2a (characterized by mutations 16145, 16316 and a back mutation at site 16362, and designated as M9a1a2a) (Table 4) were estimated by using the r statistic 44,45 with the suggested calibration rates. 44,46 RESULTS AND DISCUSSION On the basis of the combined information from control-region and partial coding-region segments, the majority (96.34%; 237/246) of the Nepalese mtDNAs could unambiguously be allocated into the defined haplogroups of East Eurasian (36.59%; 90/246), 1,[20][21][22][23][24][25] Table S1, Supplementary Material online), 5 and this pattern remains almost stable for both the East Eurasian (45.11%; 189/419) and South Asian (47.49%; 199/419) components after taking into account the recently reported Nepalese mtDNA data. 5 As for the 21 samples with ambiguously phylogenetic status, completely sequencing their mtDNA genomes revealed that virtually all of these samples in fact belong to the already defined haplogroups, such as M3, M5, M18, M30, M35, M43, D4, R8 and M60.…”
Section: Discussionmentioning
confidence: 99%
“…An mtDNA segment (spanning nucleotide position 16024-16569/1-576 and covering the whole-mtDNA control region) was amplified and sequenced as fully described in our previous works. 1,18 Mutations are recorded by comparing with the revised Cambridge reference sequence (rCRS). 19 All the individuals were allocated into specific haplogroup based on their control-region information; the assignments were further confirmed by typing additional diagnostic coding-region mutations according to the reconstructed phylogenetic trees of East Asian, 1,20-25 South Asian 5,7,12,[26][27][28][29][30][31][32][33] and Southeast Asian [34][35][36][37][38] (Supplementary Table S1, Supplementary Material online).…”
Section: Dna Amplification Sequencing and Quality Controlmentioning
confidence: 99%
See 3 more Smart Citations